2023
DOI: 10.1021/acs.est.3c04916
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Mo/Mn Atomic Regulation for Durable Acidity-Reinforced HZSM-5 Catalyst toward Energy-Efficient Amine Regeneration

Mingyue Li,
Lei Xing,
Zhongfei Xu
et al.

Abstract: Metal−molecular sieve composites with high acidity are promising solid acid catalysts (SACs) for accelerating sluggish CO 2 desorption processes and reducing the energy consumption of CO 2 chemisorption systems. However, the production of such SACs through conventional approaches such as loading or ion-exchange methods often leads to uncontrolled and unstable metal distribution on the catalysts, which limits their pore structure regulation and catalytic performance. In this study, we demonstrated a feasible st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Dynamic CO 2 capture results indicated that the regeneration heat duty of C@Mn 3 O 4 at 107 °C for catalytic SO 2 -poisoned MEA solvent exhibited a 32% decrease compared to the 107 °C blank case, while at 103 °C catalytic, it exhibited a 9.5% decrease compared to the 107 °C blank case. This performance outperformed most other reported SACs for amine regeneration 20,30,39 (Figures 2h and S11). Thermodynamic regeneration at various CO 2 partial pressures and CO 2 loading at 120 °C, based on the reference, also confirmed a 9% decrease in heat duty achieved by C@ Mn 3 O 4 (Figure S12).…”
Section: Catalytic Co 2 Desorptionmentioning
confidence: 54%
See 1 more Smart Citation
“…Dynamic CO 2 capture results indicated that the regeneration heat duty of C@Mn 3 O 4 at 107 °C for catalytic SO 2 -poisoned MEA solvent exhibited a 32% decrease compared to the 107 °C blank case, while at 103 °C catalytic, it exhibited a 9.5% decrease compared to the 107 °C blank case. This performance outperformed most other reported SACs for amine regeneration 20,30,39 (Figures 2h and S11). Thermodynamic regeneration at various CO 2 partial pressures and CO 2 loading at 120 °C, based on the reference, also confirmed a 9% decrease in heat duty achieved by C@ Mn 3 O 4 (Figure S12).…”
Section: Catalytic Co 2 Desorptionmentioning
confidence: 54%
“…Catalytic CO 2 desorption with solid acid catalysts (SACs) has been verified as a viable approach to enhance reaction kinetics. Improving the proton-coupled electron transfer (PCET) was an efficient route to design SACs with cooperative and abundant Brønsted acid sites (BASs) and Lewis acid sites (LASs). Notably, the presence of sulfonic groups (–SO 3 H) on these catalysts facilitates the creation of strong acid sites that can regulate the hydrogen-bonding network during CO 2 desorption. , Considering the low electronegativity of Mn atom compared to d electron-rich metals such as Co, Fe, and Ni, Mn exhibits a higher affinity and activity with S/N/O species. Via combating poison with poison, the migration and reconstruction of SO 2 -poisoned amine to active –SO 3 H groups on Mn sites provides a controllable route for enhancing SO 2 -resistance and CO 2 desorption of amine scrubbing technology. Moreover, proton transfer induced by acid sites surrounding transition metal-based catalysts can be usually facilitated throughout the electron transfer assisted by carbon materials’ frameworks. From the view of materials structure, core–shell micro/nano-structure composed of Mn-coupled carbon species holds promise as an appealing candidate for taking full advantage of the PCET effect, ascribed to the tunable compositions and morphology .…”
Section: Introductionmentioning
confidence: 99%
“…Bhatti et al 26 reported that an approximate 60% improvement in the CO 2 desorbed amount during MEA regeneration at 82 °C can be observed using the mesoporous HZSM-5 catalyst, which is synthesized by alkaline desilication and surfactant-induced reassembly from the micropore HZSM-5 parent. Moreover, the method of molecular sieves modified with metal elements has been widely analyzed by researchers, such as Al 2 O 3 supported on HZSM-5, 20 Zr impregnated on HZSM-5, 27 Fe-promoted SO 4 2− / ZrO 2 /MCM-41, 24 bimetal Mo/Mn doped on HZSM-5, 28 and MCM-41 modified by Fe, Al, and Mo. 29 The results revealed the composite catalyst possessed more active components, which enhanced the acid sites and catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Bhatti et al reported that an approximate 60% improvement in the CO 2 desorbed amount during MEA regeneration at 82 °C can be observed using the mesoporous HZSM-5 catalyst, which is synthesized by alkaline desilication and surfactant-induced reassembly from the micropore HZSM-5 parent. Moreover, the method of molecular sieves modified with metal elements has been widely analyzed by researchers, such as Al 2 O 3 supported on HZSM-5, Zr impregnated on HZSM-5, Fe-promoted SO 4 2– /ZrO 2 /MCM-41, bimetal Mo/Mn doped on HZSM-5, and MCM-41 modified by Fe, Al, and Mo . The results revealed the composite catalyst possessed more active components, which enhanced the acid sites and catalytic performance. , Additionally, the metal-modified molecular sieves by impregnation or ion-exchange methods can cause the deactivation of active sites during cyclic tests due to the weak connection force between active metal elements and molecular sieve carriers; also, multimetal modification molecular sieve composites inevitably reduce porosity and cause channel blockage. , Thus, the synthesis of efficient heterogeneous catalysts with abundant acid sites, high specific surface area, and excellent stability is urgently needed for the CO 2 desorption application.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Idem et al reported that the solid acid catalysts of HZSM-5 and γ-Al 2 O 3 can effectively reduce the heat duty in the regeneration of amines . Subsequently, many solid acid catalysts were developed, including zeolite molecular sieves like HZSM-5, Hβ, HY, and SAPO-34, mesoporous silica like MCM-41, , super acids like SO 4 2– /ZrO 2 /SBA-15, , metal organic frameworks, transition-metal oxides, , and their composites. These solid acid catalysts demonstrated promising performance in lowering the regeneration temperature of amine solvents and reducing the heat duty, , while the exploration of highly active solid acid catalysts remains needing. The mechanism underlying catalytic solvent regeneration by solid acid catalysts involves their participation in the carbamate breakdown, which reduced the activation energy of CO 2 desorption by providing both Bro̷nsted and Lewis acid sites (BAS and LAS) .…”
Section: Introductionmentioning
confidence: 99%